2015
DOI: 10.1152/ajpregu.00544.2014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct differences in the responses of the human pancreatic β-cell line EndoC-βH1 and human islets to proinflammatory cytokines

Abstract: While insulinoma cells have been developed and proven to be extremely useful in studies focused on mechanisms controlling β-cell function and viability, translating findings to human β-cells has proven difficult because of the limited access to human islets and the absence of suitable insulinoma cell lines of human origin. Recently, a human β-cell line, EndoC-βH1, has been derived from human fetal pancreatic buds. The purpose of this study was to determine whether human EndoC-βH1 cells respond to cytokines in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…The weak cytokine-mediated activation of NFκB in EndoC-βH1 beta cells, as in human islets, failed to induce the iNOS pathway [22,24,33], which is at variance to rodent beta cells [7,13,19,21,[34][35][36][37][38][39]. Our results confirm recent studies in EndoC-βH1 beta cells that reported virtually no expression of iNOS [4,40]. In addition, we documented a lack of expression of other NOS isoforms: endothelial NOS and neuronal NOS.…”
Section: Discussionsupporting
confidence: 87%
“…The weak cytokine-mediated activation of NFκB in EndoC-βH1 beta cells, as in human islets, failed to induce the iNOS pathway [22,24,33], which is at variance to rodent beta cells [7,13,19,21,[34][35][36][37][38][39]. Our results confirm recent studies in EndoC-βH1 beta cells that reported virtually no expression of iNOS [4,40]. In addition, we documented a lack of expression of other NOS isoforms: endothelial NOS and neuronal NOS.…”
Section: Discussionsupporting
confidence: 87%
“…Release of hsp90a by vascular smooth muscle cells can be prompted by oxidative stress, 8 and reactive oxygen species such as nitric oxide (NO) are detected in human islets exposed to cytokines. 24 Furthermore, cytokine-induced apoptosis of primary rat beta cells and the rat beta cell line INS-1E is dependent on NO production. 25 Cytokine exposure increased transcript expression for the NO-generating enzyme iNOS in human bLox5 cells and cadaveric islets ( Fig.…”
Section: Beta Cell Hsp90a Release In Response To Cellular Inos Activitymentioning
confidence: 99%
“…The EndoC-βH1 and -βH2 cells were generated from human fetal pancreatic bud and express numerous β-cell markers. These human β-cell lines respond to elevated glucose with stimulation of insulin secretion (7,8) and are increasingly used to explore various aspects of human β-cell biology (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we monitored different parameters that constitute the triggering pathway of the GSIS (1,21), the electrophysiological and ultrastructural properties of EndoC-βH1 and -βH2 cells.…”
Section: Introductionmentioning
confidence: 99%